Effects of Video Task With a High-Level Exercise Illustration on Knee Movements in Male Volleyball Spike Jump - Liu, Xiangyu; Huang, Huiming; Li, Xiaohan; Li, Jianshe; Shi, Huijuan; Wang, Aiwen (Frontiers in Psychology, 2021)
Adverse knee biomechanics including excessive knee affordance result in injuries in volleyball spike jump, which can be reconfigured by the video intervention. The aims of this study was to explore the effects of video tasks on knee in the volleyball spike jump. Fifteen elite male volleyball athletes were included. This study investigated the knee movements in sagittal, coronal, and transverse planes before and after video tasks in spike jump using both the statistical parametric mapping (SPM 1D) and discrete statistics. The results of SPM 1D indicated the larger knee flexion angle, the moment and the knee adduction angular velocity during the phase from 31.17 - 73.19 % (t=2.611, p=0.012), 19.72-21.38% (t=0.029, p=0.029) and 49.07 - 62.64% (t=3.148, p=0.004) respectively, but the smaller knee external rotation angular velocity and the vertical ground reaction (vGRF) during the phase from 45.85 - 49.96% (t=5.199, p=0.017), 3.13 - 5.94% (t=4.096, p=0.014) and 19.83 - 21.97% (t=4.096, p=0.024) respectively. With discrete value analysis, the video task increased the maximal knee flexion angle but decreased the maximal extension moment, flexion moment, abduction moment, external moment, the first peak vGRF, and loading rate. Conclusions: This study indicates that knee biomechanics in volleyball spike jump may be positively influenced by the video tasks. The video task as a means has the potential to enhance athletes' active control of the lower limbs, which improves the original movement strategies.